Meningkatkan Hasil Belajar Peserta Didik Menggunakan Model Project Based Learning Berbantuan Media Audio Visual Materi Kesederajatan Antara Perempuan dan Laki-Laki di SDN 101845 Sukamakmur - Dermawan Manik; Yohanes Subasno; Veronika Sunarningsih (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The purpose of this study was to improve the character formation of the Pancasila Student Profile (P3) and the cognitive learning outcomes of students in Catholic Religious Education and Character Education lessons on the material of equality between women and men, so that they can act correctly and appropriately through the project based learning model. This study is a classroom action research involving 7 Catholic students in phase C class 5 at SDN 101845 Sukamakmur in the 2024/2025 school year. This study was conducted in 2 learning cycles. Data collected with observation guidelines and through written tests in each cycle and analyzed descriptively qualitatively. The results of the study showed that in cycle I the average percentage of P3 character formation was 70.7 with an average cognitive learning outcome of 80 with classical completeness of cognitive learning outcomes obtained at 71.43%. In cycle II, the average percentage of character formation of P3 was 85.2 with an average cognitive learning outcome of 97.1 with classical completion of cognitive learning outcomes obtained at 100%. Thus, the application of the use of project-based learning models assisted by audio-visual media can improve the formation of the Pancasila Student Profile (P3) character and cognitive learning outcomes of students.